The role of family and school in creating a linguistic environment / Messbahul Haq, Abdul Karim Turi and Yuslina Muhammad - Haq, Messbahul; Turi, Abdul Karim; Muhammad, Yuslina (Academy of Contemporary Islamic Studies (ACIS), 2018)
The linguistic environment is an important element in the teaching of any foreign language. Because language is the emanation of the environment and its output, therefore, for learning any foreign language needs a suitable environment, for example, it is not possible; to imagine students mastering the Arabic language in schools were environment differs from the Arabic environment. The family and the school play an important role in the provision and development of the linguistic environment. This research aims to highlight the role of the family and the school and to find some important strategies in developing a desired language environment in which students learn foreign language automatically, such as the child learns language of his mother without any difficulty in education.